Prevalencia del Síndrome Antifosfolipídico como causa del aborto recurrente. - Vargas Lozada, Andrés Alejandro (2024)
The antiphospholipid syndrome is one of the few treatable obstetric pathologies when diagnosed in a timely manner, this syndrome has been related to several complications that are associated with coagulation problems or systemic autoimmune diseases that may compromise the welfare of the mother and fetus in pregnancy, childbirth or during the puerperium, In order to maintain an adequate conduct in the face of future cases, I propose the objective of determining the prevalence between antiphospholipid syndrome and recurrent miscarriages, through related bibliographic information and based on its evidence, this study refers to an investigation without manipulation of variables, since it takes into account events that occur naturally, observing the phenomenon studied and considering the behavior expressed by this pathology in pregnant women. We collected data from the past in a delimited period of time in order to analyze the results of these investigations, to integrate this knowledge in the present study, with which it is determined that the antiphospholipid syndrome is a systemic autoimmune disease, manifested by the constant presence of antiphospholipid antibodies in blood and prevails in women of childbearing age who present thrombotic events due to a state of hypercoagulability, It is reiterated in several bibliographies that the gestational state itself is catalogued as a risk factor that can contribute to the manifestation of this pathology in patients with coagulation problems or with systemic autoimmune diseases that do not present symptoms prior to pregnancy. This study considers that it is key to seek medical contact and focus our attention on preventable risk factors. Since we cannot avoid or control the presence of the antibodies responsible for this syndrome, we try to maintain a preventive behavior by educating patients about these risk factors, which will help us to avoid future complications such as recurrent miscarriages, preterm births and maternal mortality.